Substrate recognition by a peptide-aminoacyl-tRNA ligase - Josseline Ramos-Figueroa; Haoqian Liang; Wilfred A. van der Donk (Proceedings of the National Academy of Sciences, 2025)
The continuing discovery of new peptide-aminoacyl-tRNA ligases (PEARLs) has unveiled a diverse array of enzymes with the unique potential to append amino acids to the C terminus of substrate peptides in an aminoacyl-tRNA-dependent manner. To date, PEARLs have been reported that can conjugate Cys, Ala, Trp, Gly, Leu, Asn, and Thr residues, but the basis of peptide substrate and aminoacyl-tRNA recognition is not known. Cell-free expression (CFE) has emerged as a powerful tool to rapidly assay activity of substrate variants, and we used the technique in this study to investigate the peptide substrate specificity of the PEARL B h a B C T r p . This enzyme that adds Trp was discovered previously during genome mining for ribosomally synthesized and posttranslational modified peptides (RiPPs). The enzyme is remarkably tolerant of changes to the C-terminal amino acid of the peptide substrate, and truncation and replacement experiments suggest a minimal sequence requirement. An AlphaFold3 model provided insights into binding interactions of the substrate peptide BhaA-Ala to B h a B C T r p and also generated predictions for tRNA, ATP, and Mg 2+ binding modes that were tested by site-directed mutagenesis. The data suggest that several highly conserved residues in PEARLs recognize the 3′-CCA sequence present in all tRNAs. The minimal sequence required for Trp incorporation by B h a B C T r p was employed as a protein tag for C-terminal labeling of eGFP, lysozyme, and MBP with Trp and 5-Br-Trp.